PENERAPAN HACCP PADA PENGOLAHAN DAGING AYAM DI INSTALASI GIZI RSUP dr. SOERADJI TIRTONEGORO KLATEN - Eka Rachmawati; Titik Sulistyani; Lina Mufidah; Christiana Mayang (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2021)
The purpose of this research; (1)knowing the determination of the identification of the dangers of chicken meat processing; (2) knowing the conclusion of the control point of chicken meat processing; and (3) knowing the determination of critical limits of chicken meat processing. This type of research uses qualitative research. The study subjects were seven people in the nutritional installation at RSUP. Dr. Soeradji Tirtonegara Klaten. The data collection methods in this study are observations, in-depth interviews, and documentation. The results of the study are: (1) identification of the dangers of processing chicken meat is in danger of risk category VI but is still safe for consumption; (2) the point of control or the stage of setting the limit of control properly including the receipt of foodstuffs, sorting, stripping, storage, washing, processing, processing, distribution, distribution, and presentation; 3) The determination of critical limits or CCP, indicated by the determination of essential limits of biological, chemical, physical hazard parameters that must be controlled in a CCP so that it is expected to eliminate or reduce the potential dangers posed to the processing of chicken meat to the extent that can be received. The study's advice is that food processors must use personal protective equipment (PPE) to anticipate occupational safety and avoid contamination of food.